Concentric Structures and Hydrothermal Venting in the Western Desert, Egypt - Mazzini, Adriano; Lupi, Matteo; Sciarra, Alessandra; Hammed, Mohamed; Schmidt, Susanne T.; Suessenberger, Annette (Frontiers in Earth Science, 2019)
Large-scale concentric structures are enigmatic geological features present on Earth and on other planetary bodies. Their formation has been attributed to several processes. Here we describe the mapping and characterization of 100 large concentric circular structures found in Early Cenomanian argillaceous strata of the Bahariya depression (Egyptian Western Desert). The geological processes that lead to the formation of these features remained so far elusive. The whole depression is dissected by the 90 km long N60oE-striking dextral strike slip Mid Bahariya fault. Effusive lavas and shallow intrusions crop out at the footwall of the fault. The mapped circular structures increase in number approaching the fault zone. These features, similar in shape to impact craters, reach the height of 10 m, and a maximum width of 625 m, with steeper external flanks and a gently dipping internal subsided zone. We integrate field observations with laboratory analyses of rock samples. Halite-cemented brecciated sediments have been sampled in the central part of the concentric circular structures. Petrography analyses revealed also presence of high- and low-temperature minerals (e.g. Ba-K-feldspars and ferroalumino-celadonite) suggesting former hydrothermal circulation. Soil gas flux profiles (CO2 and CH4) reveal a modest CO2 increase when crossing the central part of the concentric circular structures suggesting the presence of a higher permeability. Field and laboratory data are consistent with a scenario envisaging a diffused and vigorous hydrothermal venting. The proposed formation scenario includes three main steps: 1) the pre-existing faulted damage zone provided pathways for the magma ascent to the surface and to develop a network of subsurface intrusions in the organic-rich sediments of the Bahariya Formation; 2) the interaction of the igneous intrusions with carbon-rich sedimentary deposits produced overpressured fluids, causing the formation of sparse vents manifestations at the surface as circular craters; 3) during the venting activity the shearing of the fault continued deforming and fracturing such hydrothermal vents. The elongation of the main axis of the vents and the deformed structures located within the strike slip deformation zone suggest that faulting controlled the emplacement and the final shape of some of the hydrothermal vents.